ON UNFAIR STATE ACTS IN INTERNATIONAL TRADE IN ACCORDANCE TO THE WTO LAW: THE AMBIVALENCE OF ITS DISCIPLINE AND ITS JUSTIFICATIONS - Borges, Daniel Damasio [UNESP] (Fundacao Getulio Vargas, Escola Direito, 2017)
The competition for world market shares involves not only companies, but also States. In fact, public policies are adopted in order to aid domestic enterprises to increase their share in the world market. For this reason, it is often questioned whether some State acts can be considered unfair acts, since they prevent a competition on a level playing field. The WTO law responds this question affirmatively, because it allows its members to react against dumping and subsidies. This authorization aims to protect domestic companies from unfair competition. However, this authorization does not mean that antidumping and countervailing measures are always good trade policies and free from economic costs. Therefore, the use of these trade policies instruments should be submitted to additional debate.
Keywords: World trade; unfair trade practices; WTO law; dumping; subsidies